Cross- and axial-peak intensities in 2D-SLF experiments based on cross-polarization - the role of the initial density matrix - Das, Bibhuti B.; Ajithkumar, Thalasseril G.; Sinha, Neeraj; Opella, Stanley J.; Ramanathan, K. V. (Journal of Magnetic Resonance, 2007)
Simulations and experiments on simple oriented systems have been used to estimate the relative ratio of cross-peak to axial-peak intensities in 2D-SLF experiments based on dipolar oscillations during cross-polarization (CP). The density matrix prior to dipolar evolution is considered and for an isolated spin pair, it is shown that direct calculations of the ratios match well with simulations and experimental results. Along with the standard CP pulse sequence, two other pulse sequences namely CP with polarization inversion (PI-CP) and another novel variation of the standard CP experiment (EXE-CP) reported recently have been considered. Inclusion of homonuclear dipolar coupling has been observed to increase the axial-peak intensities. In combination with Lee-Goldburg (LG) decoupling, experiments on an oriented liquid crystalline sample have been carried out and the performance of the pulse schemes have been compared. The applicability of the new pulse sequence for different samples and different nuclei is discussed. Such studies are expected to lead to a better understanding of the experiments and to the design of useful pulse sequences. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: cross polarization; oriented molecules; PISEMA; SLF